2010
DOI: 10.1097/dcc.0b013e3181f0bfd1
|View full text |Cite
|
Sign up to set email alerts
|

Subglottic Secretion Aspiration in the Prevention of Ventilator-Associated Pneumonia

Abstract: Ventilator-associated pneumonia is a common nosocomial infection that results in both negative patient outcomes and increased health care costs. Recently, many efforts have been targeted at ventilator-associated pneumonia prevention, including the practice of subglottic secretion aspiration. Six randomized control studies examining the effectiveness of subglottic secretion aspiration in the prevention of ventilator-associated pneumonia were reviewed for this article. Results consistently show that subglottic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…This means that to ensure proper practice, innovative techniques such as electronic and mechanical alarms have to be implemented, as do educational measures. 20,32,[48][49][50] Better strategies should be adopted at the bedside to eliminate erroneous behavior and attitudes. On the other hand, the implementation of some practices, such as subglottic suctioning of respiratory secretions or selective digestive decontamination, does not depend on personal knowledge or conviction, but on unit or hospital policies.…”
Section: Discussionmentioning
confidence: 99%
“…This means that to ensure proper practice, innovative techniques such as electronic and mechanical alarms have to be implemented, as do educational measures. 20,32,[48][49][50] Better strategies should be adopted at the bedside to eliminate erroneous behavior and attitudes. On the other hand, the implementation of some practices, such as subglottic suctioning of respiratory secretions or selective digestive decontamination, does not depend on personal knowledge or conviction, but on unit or hospital policies.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the second CSS includes design features to ensure that the tip of the catheter is completely clean after it is removed from the trachea. This tip cleaning feature may reduce the risk of introducing secretions into the trachea and lungs, thus also diminishing the risk of ventilator-associated pneumonia [12], [13], [14], and by maintaining a more patent airway compared to a CSS without this feature, worsening of obesity-related breathing difficulties to the point of developing MOHS [10].…”
Section: Discussionmentioning
confidence: 99%
“…Dezfulian et al [36], only found a positive association for early-onset VAP in patients requiring more than 72 h of mechanical ventilation; Muscedere et al [37] demonstrated a 50% reduction of VAP with this preventive measure; furthermore, the patients that eventually developed VAP had delayed onset pneumonia. Mortality, mechanical ventilation, and ICU duration were not affected by its implementation [37][38][39]. It is important to highlight the need for strict "cuff pressure control" to ensure effective drainage.…”
Section: Subglottic Secretions Drainagementioning
confidence: 99%